Transition metal complexes of imidazole appended pyridyline linked bisphosphine, 2,6-bis(2-(diphenylphosphanyl)-1H-imidazol-1-yl)pyridine - Saurabh Kumar; Maravanji S. Balakrishna (Results in Chemistry, 2021)
Large-bite, bisphosphine, 2,6-bis(2-(diphenylphosphanyl)-1H-imidazol-1-yl)-pyridine (BDIP) on treatment with [Mo(NC5H11)2(CO)4], [Ni(PPh3)2(CO)2] and [M(COD)Cl2] [M = Pd, Pt] afforded corresponding chelate complexes [{2,6-{PPh2C3H2N2}2C5H3N}{Mo(CO)4}] (2), [{2,6-{PPh2C3H2N2}2C5H3N}{Ni(CO)2}] (4) and [{2,6-{PPh2C3H2N2}2C5H3N}{MCl2}] [5, M = Pd; 6, M = Pt]. Treatment of BDIP with one equivalent of [Ru(η6-p-cymene)Cl2]2 resulted in a dinuclear complex [{2,6-{PPh2C3H2N2}2C5H3N}{Ru(η6-p-cymene)Cl2}2] (3). The ligand bite varies in the range 97.46(4)° (2) to 104.07(2)° (6), whereas the M−P bond distances, P···P separation and dihedral (twist) angles are in the range of 2.2–2.5 Å, 3.534–3.841 Å and –54° to 120°, respectively. The structures of 2, 3, 5 and 6 were confirmed by single crystal X-ray analysis.